Итоги раскопок техногенного участка на Картамышском рудопроявлении - Бровендер, Ю. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Yu. Brovender. Technogenic section of the pit Chervone ozero-I of the Kartamysh archaeological micro-district (some results of the research) The results of the research of one of the components of Kartamysh archaeological complex (Bachmutskaya hollow of Donetsk basin) — technogenic section of the pit Chervone ozero–I are considered in the article. Basic massif of sources which was revealed in the technogenic section area was connected with the mining-concentrating activity, the aim of which was the obtaining of the copper-ore concentrate for the metallurgical production. Besides, there are evidences of mine and metallurgical cycles of the metallurgical production. The materials which represent complicated system of the production cult of ancient Donbass mine-metallurgists were found in the technogenic section. Functioning of the monument is connected with the massif activity of the population of stepanovsky type of the berezhnovsko-maevskaya timber-grave culture.